2003
DOI: 10.1161/01.cir.0000096484.03318.ab
|View full text |Cite
|
Sign up to set email alerts
|

Reinduction of T-Type Calcium Channels by Endothelin-1 in Failing Hearts In Vivo and in Adult Rat Ventricular Myocytes In Vitro

Abstract: Background-In ventricular myocardium, the T-type Ca 2ϩ current (I Ca,T ), which is temporarily observed during fetal and neonatal periods, has been shown to reappear in failing/remodeling hearts. However, its pathophysiological regulation has not been elucidated. Methods and Results-We utilized Dahl salt-sensitive (DS) rats with hypertension at the stage of concentric left ventricular (LV) hypertrophy (11 weeks old, LVH) and at the heart failure stage (16 to 18 weeks old, CHF). Some were treated with bosentan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…31 In addition, angiotensin II also exerts direct cellular electrophysiological effects on cardiomyocytes that favor the development of AF. 32 Experimental studies have shown that angiotensin II modulate the expression of multiple ion channels, including the L-type and T-type calcium current (I Ca, T , I Ca, L ), 33,34 the rapid and slow component of the delayed rectifier potassium currents (I Ks , I Kr ), 35 and the transient outward potassium current (I to ). 36 These changes in the expression of ion channels as well as alteration of calcium handling in atrial cardiomyocytes can promote the development of AF.…”
Section: Raas Activationmentioning
confidence: 99%
“…31 In addition, angiotensin II also exerts direct cellular electrophysiological effects on cardiomyocytes that favor the development of AF. 32 Experimental studies have shown that angiotensin II modulate the expression of multiple ion channels, including the L-type and T-type calcium current (I Ca, T , I Ca, L ), 33,34 the rapid and slow component of the delayed rectifier potassium currents (I Ks , I Kr ), 35 and the transient outward potassium current (I to ). 36 These changes in the expression of ion channels as well as alteration of calcium handling in atrial cardiomyocytes can promote the development of AF.…”
Section: Raas Activationmentioning
confidence: 99%
“…Reexpression of T-type current has also been reported in pressure-overloaded rat and mouse hearts, in many different models of heart failure, and after myocardial infarction injury (12)(13)(14)(15)(16). More recently, reinduction of T-type current in the failing rat heart was shown to be dependent on endothelin-1 signaling (17). Reexpression of T-type current in the diseased myocardium conducts additional Ca 2+ influx during the action potential, although the function of this Ca 2+ influx remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…low-voltage-activated calcium channel; oxidative stress; cardiomyocytes SINCE THE INITIAL BIOPHYSICAL (34) and molecular characterization (5, 27, 36) of low-voltage-activated T-type calcium currents in heart and neurons, these channels have been studied in various systems and pathological conditions. T-type currents are reexpressed in the adult hypertrophied ventricle and in postmyocardial infarction (18), in the monocrotaline model of pulmonary hypertension and heart failure (24,44), and in vitro in adult ventricular myocytes exposed to 10% FBS (9) and endothelin-1 (19), relating the T-type current to the pathology rather than to normal physiological function of the myocytes. The mechanisms for regulation of the T-type channels are incompletely characterized, largely due to the lack of specific inhibitors and the presence of the more robust L-type and store-operated calcium channels, which make it difficult to isolate T-type Ca 2ϩ channel functions, such as secretion (29), excitation (52), or transcription regulation (4).…”
mentioning
confidence: 99%
“…Less is known about the pathways involved in Ca v 3.1 ␣-subunit regulation, although there is evidence that Ca v 3.1 mRNA is increased in adult ventricular myocytes exposed to endothelin-1 (19). Also, heterologously expressed Ca v 3.1 membrane currents can be increased when coexpressed with the L-type calcium channel auxiliary ␣ 2 ␦-subunit (13) or decreased by the ␥ 6 -subunit (16).…”
mentioning
confidence: 99%